Literature Review of Cement Matrices and Fibers Used in SIFCON - Ahmed, Ahmed Dalaf; Al-Kubaisi, Ghassan; Al-Taie, Entidhar; Ismail, Abdulkader (International Journal of Sustainable Construction Engineering and Technology, 2023)
Conventional concrete is categorized as brittle. As a result, researchers continued working to develop it into a substance having ductile characteristics. Concrete showed remarkable improvement when fiber was incorporated at a ratio of 1-2%. Slurry-infiltrated fiber concrete (SIFCON) allows for the use of up to 20% more fiber when combined with unique cement slurry. Concrete that was produced had increased strength and ductility. The influence of slurry and fiber forms with different volumes on the resistance of concrete to compression, flexural, shear, and bond was the main focus of this review study. The outcomes of several previous investigations revealed a significant relationship between the strength of concrete and the slurry mixture, fiber type, and fiber volume. Additionally, it was shown that the majority of research all agreed that certain methods should be followed when employing a volume of more than 5% fiber. These processes entail employing fine-sand less than 1 mm in size to create a suitable cement slurry and replacing up to 30% of the cement with fly ash (FA), silica fume (SF), and metakaolin to create a cement slurry capable of penetrating interlocking with fiber of all forms and volumes.